Pencegahan Stigma Terhadap Orang dalam Penyebutan Covid-19 - Dewantari, Nustin Merdiana; Ula, Shofiatul; Muharni, Yusraini; Susilo, Sidik (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
There are still many people who do not know and understand the COVID-19 virus, which is still new. Some of the news that can be accessed on news search links show a lot of oppression and stigma against people called COVID-19. Stigma, among other things, arises because society ignores new diseases and there is no cure, stigma can be suppressed and lost if society finds out about it. Generally, service activities are conducted to provide knowledge and understanding of COVID-19 and how to prevent it. Stigma prevention is done by environmental disinfection activities, mask distribution for adults and children as well as counseling on clean and healthy living habits and physical distance, disinfection activities and mask distribution done to give a sense of peace to the population. Clean and healthy lifestyle guidance activities and physical distance are done to provide correct information. Generally, service activities are conducted to provide knowledge and understanding of COVID-19 and how to prevent it. With the right knowledge, stigma will not occur in society. This service can improve people's knowledge and understanding of COVID-19, live a new life pattern, and understand the attitudes and views that should be present when dealing with people called COVID-19 so that people can live their daily lives calmly and vigilantly